Influence of occlusal loading force on occlusal contacts in natural dentition. Issue 2 (April 2015) - Imamura, Yoshiki; Sato, Yuji; Kitagawa, Noboru; Uchida, Keiichiro; Osawa, Tokiko; Omori, Miyuki; Okada, Yukihiko
Abstract Purpose Proper occlusal contact is important for the long-term success of prosthodontic therapy. We clarified the effects of occlusal loading force on occlusal contact in natural dentition by comparing measured values for occlusal loading and occlusal contact area. Methods Masseter muscle activity was measured in 10 subjects (2 male, 8 female; mean age, 27 years) with natural dentition using electromyography, with clenching at full strength with nothing interposed between the upper and lower teeth defined as 100% maximum voluntary contraction (MVC). Pressure-sensitive film (Occluzer) was used to examine occlusal contact points at 20, 40, 60, 80, 100 and 120% MVC. A material for checking accuracy of fit (BiteEye) was used to examine occlusal contact points at 20, 40, 60 and 80% MVC. ANOVA and the Bonferroni method were used to assess the results, with the level of significance set at 5%. Coefficients of variation (CV) were also calculated by dividing the standard deviation by the mean. Results Occlusal loading and occlusal contact area increased with clenching strength; however, CV showed differences between the methods at low and high MVC. Conclusions With Occluzer, testing should be carried out at clenching strength ≥60% MVC. With BiteEye, testing should be carried out from light clenching strength at 20% MVC to moderate clenching strengths at 40–60% MVC. Occluzer and BiteEye (10 μm) gave similar occlusal contact areas at 60–80% MVC. These results suggest that combined use of Occluzer and BiteEye gives an accurate picture of occlusion from weak to strong clenching strength.